Protecting the health of children by mandating vaccination and immunization: An application of usuli principle of istihsan - Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini (2017)
In 2016, the deaths of five children from diphtheria provoked an outcry among doctors and spurred calls for an edict by religious authorities to compel Muslim families to immunize their children. In relation to this issue, the Islamic Medical Association Malaysia (IMAM) has made a statement about a need to have the Malaysian children vaccinated as vaccination is proven to prevent infection. The association took a serious view of the recent cases of diphtheria, which had not appeared in Malaysia for a long time. What is more worrying is the fact that more children in Malaysia are falling victim to contagious diseases as parents reject immunization programmes for fear the vaccines used infringe strict religious rules. In Islam, the stringent halal requirement can be waived if suitable vaccines are not available. By applying the principle of Islamic jurisprudence, although the vaccines contain a composition that is not permissible in Islam, for a reason of protection of health of children, it may be used for vaccination. There is an usuli principle of istihsan, which authorizes departure from an established ruling in favour of a different ruling as the latter is considered better on the basis of the Qur‘an, Sunnah, Ijma‟, custom, necessity or maslahah. In this paper, Islamic legal research methodology is adopted. It involves a study of the relevant literature on the law (fiqh), the Qur‘anic exegesis, the traditions of the Prophet Muhammad (hadith) and opinions of the four major schools of shariah relating to the principle of usul fiqh. The aim of this paper is to discuss the views of Muslim jurists on the application of istihsan as to whether or not vaccination and immunization should be made compulsory in order to protect the health of children in Malaysia.